Analisis Pengaruh Pelayanan Administrasi Publik Terhadap Pertumbuhan Ekonomi di Desa Parigi Kecamatan Cikande Kabupaten Serang - Fadilah, Ulvia; Soleha, Siti (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to analyze the effect of public administration service quality on economic growth in Parigi Village, Cikande District. A quantitative approach was used by measuring five dimensions of public service quality, namely reliability, responsiveness, confidence, empathy, and tangibility, based on the SERVQUAL model developed by Parasuraman, Zeithaml, and Berry (1988). Data were collected through a questionnaire with 100 respondents who were users of administrative services in the village. The results show that the dimensions of reliability and responsiveness have a significant influence on the smooth running of community economic activities, especially in terms of completing administrative documents that support small and medium enterprises. The confidence dimension reflects a fairly high level of community trust in the competence and professionalism of service officers, although improvement is still needed in the aspect of technical knowledge. The empathy dimension shows that the community feels valued and cared for in the service, although individual attention to specific needs still needs to be improved. Meanwhile, the tangible dimension highlights the need to improve the comfort of physical facilities and the professionalism of officer appearance to support a better service experience. The conclusion of this study is that quality public administration services contribute significantly to economic growth in the country